ANALISIS PERAN ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR DI RUMAH PADA MASA PANDEMI COVID 19 DI KELAS RENDAH KELURAHAN PAGAR DEWA KECAMATAN SELEBAR KOTA BENGKULU - Fitriani, Sahli; Nirwana, Evi selva (UIN Fatmawati Sukarno Bengkulu, 2023)
This research raises the issue of the role of parents in accompanying children to study at home during a low-grade pandemic at RT 51 Pagar Dewa Village, Selebar District, Bengkulu City. Qualitative research methods. The research subjects in this study were parents, the data collection techniques used were observation, interviews and documentation. Conclusion of the research results: From the results of the study it showed that the role of parents in accompanying children to study at home during a low-class pandemic in RT 51 Pagar Dewa Village, Selebar District, Bengkulu City, it can be said that some parents have completed it well, including as a facilitator for children such as providing learning tools, learning places, learning media. As a teacher, namely helping children's learning activities such as understanding material, managing children's study time, overcoming children's difficulties in learning, and providing motivation. Parents also act as educators and teachers, and as mentors.